Blockchain and IoT approaches for secure electronic health records (EHR) - Saini, Kavita 1976-; Singh, Jitendra 1970- (IGI Global, 2024)
In the realm of healthcare, the persistent challenges of data breaches, centralized systems, and fraudulent claims have posed significant hurdles in ensuring the integrity and security of patient information. The traditional approaches to managing Electronic Health Records (EHR) often fall short, leaving room for exploitation and compromising the confidentiality of sensitive medical data.Enter the transformative solution presented in Blockchain and IoT Approaches for Secure Electronic Health Records (EHR). This groundbreaking book navigates the intricate landscape of healthcare technology, addressing the vulnerabilities in the current systems. By leveraging the power of Blockchain technology, it pioneers a secure peer-to-peer communication system that not only ensures the tamper-proof nature of health records but also revolutionizes the entire healthcare industry. The book is a comprehensive exploration of Blockchain's relevance in healthcare, covering the architecture, scope, and applications that promise to redefine how patient data is managed and protected.